Stories in midwifery: Reflection, Inquiry, Action - Cummins, Allison; Gillett, Katharine; McLaughlin, Karen; Musgrave, Loretta; Wood, Jessica (Chatswood : ELSEVIER, 2023)
This insightful book and accompanying video resource present a collection of perspectives relating to different issues around birthing and midwifery. Through the voices of mothers, midwives, students, health professionals and family members, you will build empathy and understanding, reflect, and learn to apply innovative approaches in your own practice. The book covers a range of topics, such as midwifery continuity of care, place of birth, multiple pregnancy, complex pregnancies, congenital birth abnormalities, supporting culturally and linguistically diverse women, anxiety and depression, and working with women with physical and/or intellectual disabilities.
Obsahuje kód s prístupom ku e-knihe s 35 video "osobnými príbehmi"
Obsahuje biografické údaje o autoroch
Obsahuje bibliografie a bibliografické odkazy
Ideal for students and practising midwives alike. Readers will develop the skills, attitudes and mindfulness necessary for working in partnership with women, childbearing people and their families across a variety of settings.
Keywords: pôrod; asistencia pôrodná -- metódy; duly (pôrodníctvo); asistentky pôrodné; reflexia kognitívna; príbehy osobné, ako téma; gravidita; u ženského pohlavia; učebnica; príbehy osobné